2019
DOI: 10.1097/spv.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Health Information Available on the Internet for Patients With Fecal Incontinence

Abstract: Objective The aim of this study was to assess the quality of information available through the Internet for a variety of search terms for fecal incontinence (FI). Methods Using the Google search engine, searches were performed for 4 terms: “bowel control problem,” “accidental bowel leakage,” “fecal incontinence,” and “leaking stool.” The DISCERN quality analysis tool and JAMA benchmark criteria were implemented by 2 independent reviewers to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Society- and government-sponsored websites often do not make it to the top of search results despite having the highest-quality content. Prior studies have reported similar results when evaluating websites pertaining to pelvic organ prolapse, fecal incontinence, and urinary incontinence with a variable quality of evidence among websites and varying results based on search term used 13–16 …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Society- and government-sponsored websites often do not make it to the top of search results despite having the highest-quality content. Prior studies have reported similar results when evaluating websites pertaining to pelvic organ prolapse, fecal incontinence, and urinary incontinence with a variable quality of evidence among websites and varying results based on search term used 13–16 …”
Section: Discussionmentioning
confidence: 84%
“…Prior studies have reported similar results when evaluating websites pertaining to pelvic organ prolapse, fecal incontinence, and urinary incontinence with a variable quality of evidence among websites and varying results based on search term used. [13][14][15][16] Strengths of our study include the use of well-established and validated tools to evaluate websites. We used 2 independent evaluators per search term and averaged the ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation